PEMBELAJARAN PADA ERA COVID-19 DI SEKOLAH DASAR NEGERI GUGUS JAYA BAYA KECAMATAN DEMPET KABUPATEN DEMAK - Setiyowati, Endang; Kanzunuddin, Moh (Journal Prakarsa Paedagogia, 2022)
This study aims to describe: 1) the implementation of learning, 2) the problems of the teacher during learning, 3) the solutions made by the teachers on the implementation of learning during the covid-19 pandemic and 4) the role of parents in assisting children at home. This study uses a qualitative approach. Sources of data were obtained from interviews with teachers and parents of SD Negeri Gugus Jayabaya students, Dempet District. The data analysis technique used interactive analysis by Miles and Huberman. The results of this study indicate that: 1) The implementation of learning has been going well despite the Covid-19 pandemic, 3) There are several problems, namely (a) The location of the house is far from the internet network and the students' internet quota is limited, (b) The learning media is monotonous, (c) Learning is not yet interactive, (d) The character of students is difficult to monitor, (e) The learning tends to be online assignments, (f) The assignments given by students are piled up. (g) Absorption of subject matter is very minimal, (h) Assessment lacks integrity, 4) Solutions, namely (a) temporarily moving locations and joining friends, (b) using varied and interactive learning media. (c) using zoom meetings, google meet, webinars (d) giving material early, (e) submitting assignments early. (f) use of varied and live online media (h) use of varied and live online media, 5) The role of parents as educators, motivators, facilitators and mentors.